Monitoring and measuring noise pollution in urban environments (Case study: Khorramabad city - Ali Jafari; Mansour Ghaderpoori; Samira Saadati; Faramarz Azimi (Journal of Air Pollution and Health)
Introduction: Environmental noise, caused by traffic, leads to increased risk of health problems. Nowadays, noise pollution is one of the most important problems in the communities which adversely affects the health. The aim of this study was to assess the noise pollution in Khorramabad city. Materials and methods: To measure the noise level in the city, 39 stations near to sensitive places such as hospitals, educational centers, and so on were selected. Measurements were performed, for 30 min, in the mornings (7-10 AM) and evenings (5-8 PM) using a standard sound level meter. The measurements were made on working days during the week and assuming the traffic load was the same. Results: The sound level in all 39 considered stations was higher than the standard of residential-commercial in more than 90% of the stations compared to the environmental standard. The mean of sound measured in the monitored stations was equal to 68.28±2.6 dB. The maximum measured sound level belonged to station S2. In station S2, the maximum measured sound was reported as 81.72±11.3 dB. The findings showed that sound level in the evenings were slightly higher than the mornings. Also, in the evening, the highest and lowest measured sound values belonged to stations S1 and S20. The amount of measured sound level at stations S1 and S20 was equal to 80.9 and 39.7 dB, respectively. Based on findings, the highest and lowest sound recorded belonged to stations S39 and S20 which area type of stations S20 and S39 was commercial and residential, respectively. Conclusion: This study showed that the average level of sound pressure was higher than the permissible limit, so the necessity of planning is suggested to reduce the level of noise pollution and consequently reduce the anxiety level of citizens and increase health.